Contemporary fictions of attention : reading and distraction in the twenty-first century - Bennett, Alice, 1982- (Bloomsbury Academic, Bloomsbury Publishing Plc, 2018)
"With the supposed shortening of our collective attention spans, what future is there for long narrative fiction in the age of the internet? Contemporary Fictions of Attention maps out a shared interest in attention within 21st-century fiction and connects this interest to a series of debates surrounding ethics, work, the everyday, boredom and entertainment, as well as a broader context for the future of the book, fiction and reading itself in an increasingly digital culture. Alice Bennett examines work by writers including Joshua Cohen, Ben Lerner, Tom McCarthy, Ali Smith, Zadie Smith, and David Foster Wallace, and argues that they are all writing 'fictions of attention' ") --